Implementation of the REACT Strategy Assisted by PhET Simulation to Improve Critical Thinking Skills on the Mechanical Wave Characteristics Topic - Ratu Zachrien Qalbia Dwi Ridwan; Ida Kaniawati; Heni Rusnayati (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study examines the improvement of students' critical thinking skills through the REACT Strategy assisted by PhET Simulation. The research employs a quantitative method with a pre-experimental one-group pretest-posttest design. The sample consists of 35 purposively selected 11th-grade students from a high school in Bandung, studying the characteristics of mechanical waves. Instruments include an essay-based critical thinking test (eight questions), and Student Worksheets. Data were analyzed using N-Gain and effect size. Results show that the REACT Strategy with PhET Simulation yielded an N-Gain of 0.52 (medium category). The strategy was also effective in enhancing critical thinking skills, with a high effect size (d = 3.19).  In conclusion, implementing the REACT Strategy assisted by PhET Simulation significantly improves students' critical thinking skills in learning.